Prospective changes in primary care patients' family communication after skin cancer genetic test offer - Salafia, Caroline; Banerjee, Smita; Hamilton, Jada G.; Schofield, Elizabeth; Li, Yuelin; Buller, David B.; Hunley, Keith; Sussman, Andrew L.; Guest, Dolores D.; Kaphingst, Kimberly A.; Berwick, Marianne; Hay, Jennifer L. (PEC innovation, 2025)
Given the promise of family communication to prompt cancer risk awareness, we examined how an offer for skin cancer genetic testing may prompt family cancer communication. Primary care patients (N = 415, 45 % Hispanic) in New Mexico were randomized to a melanocortin-1 receptor (MC1R) genetic test invitation or usual care. We assessed whether family communication (frequency, targets of communication, and topics) differed based on whether participants were randomized to usual care, refused genetic testing, were tested and received either average- or higher-risk feedback. Findings showed no significant differences in frequency of family communication based on intervention exposure. Those who were tested and received higher-risk feedback displayed the highest levels of communication with certain targets, such as fathers. Some communication topics, such as the participant's risk of skin cancer, were discussed more by participants who were tested (both average- and higher-risk feedback) than those in usual care. Findings highlight that an offer for skin cancer genetic testing may prompt aspects of family communication, such as discussion surrounding personal skin cancer risk. This study examined various elements of family communication after an offer for skin cancer genetic testing. •Skin cancer genetic testing may catalyze some elements of family communication.•Genetic testing may raise risk awareness among individuals and their families.•Those who received testing were more likely to discuss their risk with family.